Technique in University Artist Education. A Discursive and Psychoanalytical Study - Pastorino, Magali (2024)
This communication presents the results of an investigation in education that sought to know the effects of technique in the relationship with knowledge during the process of creating a group of visual arts university students. Likewise, the discussion of the notion of subject that psychoanalysis introduces in the social sciences is incorporated, which supports the meaning of the relationship with knowledge, and its effect on the applied methodology is reviewed. The methodology is qualitative, the design is flexible, and the approach is discursive. The main results that it yields are the pregnancy in the creative process of the modern technical conception in artistic education with a productive approach, the existence of a discursive psychologicalist scheme that organizes the process and the empirical confirmation of a split position of the artist with respect to his work. product of the condition that prints the modern sense of technique.